2018
DOI: 10.1016/s1348-8643(18)30003-x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors in securing successful surgical resection of oral squamous cell carcinoma

Abstract: The purpose of this retrospective study was to analyze the factors that had a significant effect on securing a successful surgical resection (surgical margin) in oral cancer surgery. One hundred forty‐eight consecutive patients who underwent planned radical resection of oral squamous cell carcinoma (SCC) were analyzed. Successful resection was judged if pathological examination of the surgical specimen revealed a clear surgical margin (no SCC within 5 mm, n = 116), while an unsuccessful resection was judged if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Almost 15% of cases in the present study demonstrated invaded surgical margins, similar to findings in previous studies (17–44% inadequate surgical margins) ( 11 , 99 101 ); however, one study reported a lower proportion of invaded margins (7.5%) ( 28 ). In OSCC, assessing surgical margins is a crucial part of determining the therapeutic outcome, while also considering tumor location, tumor stage, tissue shrinkage and mucosal elasticity ( 102 ).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Almost 15% of cases in the present study demonstrated invaded surgical margins, similar to findings in previous studies (17–44% inadequate surgical margins) ( 11 , 99 101 ); however, one study reported a lower proportion of invaded margins (7.5%) ( 28 ). In OSCC, assessing surgical margins is a crucial part of determining the therapeutic outcome, while also considering tumor location, tumor stage, tissue shrinkage and mucosal elasticity ( 102 ).…”
Section: Discussionsupporting
confidence: 91%
“…It also has been acknowledged as enormously impactful on the survival outcomes of patients treated surgically for oral cancer ( 127 ). In previous studies, the ability to achieve a wide free margin was linked with some clinical aspects, such as age, sex, the epicenter of the tumor, T and N status, and treatment modality ( 11 , 99 , 125 , 126 , 128 , 129 ). However, occasionally, oral surgeons cannot acquire an adequate surgical margin for OSCC, as the oral cavity has a complicated anatomy, and wider resection might cause more significant disfiguration or functional disability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GLOBOCAN 2020, a database of global cancer statistics, reported that 377 713 people were newly diagnosed with lip and oral cancer in 2020 1 . Currently, the most common treatment for these cancers is complete surgical removal 2–4 . However, these surgeries can have complications including impairment of mastication, swallowing, and articulation.…”
Section: Introductionmentioning
confidence: 99%